The impact of textual input enhancement and explicit rule presentation on Iranian Elementary EFL Learners` intake of simple past tense. - Nahavandi, Naemeh; Mukundan, Jayakaran (Canadian Center of Science and Education, 2013)
The present study investigated the impact of textual input enhancement and explicit rule presentation on 93 Iranian EFL learners’ intake of simple past tense. Three intact general English classes in Tabriz Azad University were randomly assigned to: 1) a control group; 2) a TIE group; and 3) a TIE plus explicit rule presentation group. All participants were given 3 reading texts and comprehension questions to complete. For participants in groups 2 and 3 the input was textually enhanced through bolding. Participants in group 3 in addition had explicit rule presentation of simple past tense. Intake of simple past tense was measured through performance on a Multiple-Choice Recognition Tests. The results showed that there was a significant difference among pretest, first posttest and delayed posttest. Posttest 1 was significantly higher than posttest 2. Furthermore, TE+ rule presentation group significantly outperformed the control group in both posttest1 and posttest 2. The study concluded with some pedagogical implications.